(untitled) (Global Journal of Management and Business Research, 2016)
The success and the failure of any business depend upon the behavior of customers in a specific market. Hence the centre of all marketing activities is the customer. It is always difficult to understand and to predict consumers’ behavior in urban and rural areas (Kashyap, Pardeep & Siddhartha). India is a highly populated country. Its population is approximately 15% of the whole world. It has a population about 1.21 billion (census 2011). About 68.84% of total population live in 6, 40,867 villages and rest of population live in urban areas. India has 2.4% 0f world geographical areas, 4% water resources and about 15% of live stock and all this require more production to feed increasing population and livestock. Now starts the role of agriculture and that depends upon farm mechanization and farmers. Penetration of tractor in agriculture is imperative. Tractor is a mean of production, cultivation, transport, construction, electricity generation, and is also used for non agricultural purposes. India is an agricultural country with 68.86% rural population where 48.16% people get employment. Thus, agriculture directly impact Indian economy. Indian rural market includes more than 740 millions consumers and it adds about one million new consumers in market every year. Thus its potentials are very important and very lucrative for the marketers.